2008
DOI: 10.1038/nsmb.1381
|View full text |Cite|
|
Sign up to set email alerts
|

Single-molecule studies of fork dynamics in Escherichia coli DNA replication

Abstract: We present single-molecule studies of the replication machinery of Escherichia coli and describe the visualization of individual E. coli DNA polymerase III (Pol III) holoenzymes engaging in primer extension and leading-strand synthesis. When coupled to the replicative helicase DnaB, Pol III mediates leading-strand synthesis with a processivity of 10.5 kb, 8-fold higher than that of primer extension by Pol III alone. Addition of the primase DnaG to the replisome causes a 3-fold reduction in the processivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(165 citation statements)
references
References 50 publications
10
145
1
Order By: Relevance
“…1 C and D) and rate ( Fig. 2A) of each synthesis step were generated from a large number of events; the data were in agreement with previous single-molecule experiments for Pol III (22) and bulk data for Pol IV (23). Pauses between synthesis steps were exponentially distributed, consistent with a single rate-limiting step, and we observed that increasing the concentration of Pol III from 5 to 30 nM reduced the pause length ( Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…1 C and D) and rate ( Fig. 2A) of each synthesis step were generated from a large number of events; the data were in agreement with previous single-molecule experiments for Pol III (22) and bulk data for Pol IV (23). Pauses between synthesis steps were exponentially distributed, consistent with a single rate-limiting step, and we observed that increasing the concentration of Pol III from 5 to 30 nM reduced the pause length ( Fig.…”
Section: Resultssupporting
confidence: 74%
“…S2 A-C, time constant τ decreases from 19.7 to 12.4 s). Biophysical and structural data suggest that only one Pol III binds the clamp dimer (4,18,24,25), arguing that pauses observed during synthesis result from stochastic dissociation of Pol III from the clamp and the diffusionlimited recruitment of a new polymerase from solution (22).…”
Section: Resultsmentioning
confidence: 99%
“…Similar experiments were performed on the leading-strand synthesis complex of E. coli (104). Here also, the processivity of the leadingstrand synthesis complex (10.5 kb) was significantly higher than that of the DNA polymerase alone (1.4 kb), pointing to an increase in stability when more factors that provide additional protein-protein and DNA-protein interactions are added.…”
Section: Figuresupporting
confidence: 62%
“…The frequency of interaction between DnaG and DnaB controls the length of the Okazaki fragments (116,124). Single-molecule experiments on the E. coli leading-strand synthesis complex demonstrated that the association between DnaG and DnaB resulted in a cessation of fork progression (104), analogous to the pausing behavior observed in the T7 system (64). The reduction in processivity was cooperative with respect to the primase concentration when primer synthesis was allowed (104).…”
Section: Dna Primase Activitymentioning
confidence: 97%
“…Processivity estimates of the E. coli replisome from ensemble studies indicate a lower limit of 50 kb, and an average bulk rate of Ϸ500-700 nt/s at 37°C (6,7). Processivity measurements from other recent single-molecule studies differ over a wide range, from 3 kb to Ͼ80 kb (8,9). In each of these previous studies replication was performed in the presence of excess proteins that could replace a replisome protein that dissociates from DNA, and thus the true processivity of the replisome has not been examined.…”
mentioning
confidence: 99%